IIR and FIR digital filter : a case study - Zainal, Fathiah; Hashim, Nik Mohd Zarifie; A Aziz, Khairul Azha; Salleh, Azahari; Mohamad, Najmiah Radiah; Ja'afar, Abd Shukur (IJARET, 2015)
This paper is about to analyze and identify the digital audio signal. Two audio signals are provided which is the original audio and the added noise audio signal. The purpose of the study is to identify and eliminate the unknown noise signals by using Finite Impulse Response and Infinite Impulse Response digital filters. The detail steps to design the both have been stated in this paper. All the results is simulated and showed in MATLAB to show the comparison between the two. Keywords- FIR, IIR, MATLAB,